Analysis of Family Behavior with the Incidence of Stunting in Toddlers Aged 3-5 Years - Mikawati; Evi Lusiana; Suriyani (Journal of Bionursing, 2023)
Introduction : Currently, stunting is one of the government's main concerns, because cases of stunting are increasing in Indonesia. The prevalence of stunting, which is in the high category, will affect growth and development failure in toddlers and will affect economic status if not taken seriously. One effort that can be done is to increase family empowerment, both through knowledge and attitudes and behavior.Objective: This study aims to determine family behavior with the incidence of stunting in toddlers aged 3-5 years, where the family behavior variables consist of Clean and Healthy Behavior (PHBS), family behavior in food processing, and family behavior in feeding. Research Methods: In this study using a descriptive research design with a cross sectional study approach. The respondents were mothers who had stunted toddlers aged 3-5 years in the working area of ​​the Kaluku Bodoa Health Center, with a purposive sampling technique of 68 samples. Results: From the data analysis using SPSS with the chi square test, the results showed that there was a relationship between family PHBS behavior in food processing and feeding with the incidence of stunting in toddlers aged 3-5 years. As for each value p is p1 = 0.014, p2 = 0.012 and p3 = 0.000. Conclusion: from the results of this study, it can be concluded that the family is one of the factors that can reduce the incidence of stunting, for this reason it is necessary to increase government programs, especially in health centers that involve families in efforts to prevent stunting.